Exosomal miR-485-3p derived from pancreatic ductal epithelial cells inhibits pancreatic cancer metastasis through targeting PAK1. Issue 19 (5th October 2022) - Li, Mingzhe; Zhou, Jiaxin; Zhang, Zhengkui; Li, Jisong; Wang, Feng; Ma, Ling; Tian, Xiaodong; Mao, Zebin; Yang, Yinmo
Abstract: Background: Cell competition is an important feature in pancreatic cancer (PC) progression, but the underlying mechanism remains elusive. This study aims to explore the role of exosomes derived from normal pancreatic ductal epithelial cells involved in PC progression. Methods: PC cells and pancreatic stellate cells (PSCs) were treated with exosomes isolated from pancreatic ductal epithelial cells. Cell proliferation was assessed by CCK8 assays. Cell migration and invasion were assessed by Transwell assays. PC and matched adjacent non-tumor tissue specimens were obtained from 46 patients pathologically diagnosed with PC at Peking University First Hospital from 2013 to 2017. Tissue miR-485-3p and p21-activated kinase-1 (PAK1) expression was examined by real-time polymerase chain reaction (RT-PCR), and the relationship of the two was analyzed using Pearman's product-moment correlation. The clinical significance of miR-485-3p was analyzed using the Chi-square test, Wilcoxon rank-sum test, and Fisher exact probability, respectively. The binding of miR-485-3p to PAK1 5′-untranslated region (5′-UTR) was examined by luciferase assay. PC cells were xenografted into nude mice as a PC metastasis model. Results: Exosomes from pancreatic ductal epithelial cells suppressed PC cell migration and invasion as well as the secretion and migration of PSCs. MiR-485-3p was enriched in the exosomes of pancreatic ductal epithelial cells but deficient in those of PC cells and PSCs, in accordance with the lower level in PSCs and PC cells than that in pancreatic ductal cells. And the mature miR-485-3p could be delivered into these cells by the exosomes secreted by normal pancreatic duct cells, to inhibit PC cell migration and invasion. Clinical data analysis showed that miR-485-3p was significantly decreased in PC tissues ( P < 0.05) and was negatively associated with lymphovascular invasion ( P = 0.044). As a direct target of miR-485-3p, PAK1 was found to exert an inhibitory effect on PC cells, and there was a significantly negative correlation between the expression levels of miR-485-3p and PAK1 ( r = −0.6525, P < 0.0001) in PC tissues. Moreover, miR-485-3p could suppress PC metastasis in vivo by targeting p21-activated kinase-1. Conclusions: Exosomal miR-485-3p delivered by normal pancreatic ductal epithelial cells into PC cells inhibits PC metastasis by directly targeting PAK1. The restoration of miR-485-3p by exosomes or some other vehicle might be a novel approach for PC treatment.